Epoxidized natural rubber coated lithium battery positive electrode active material as well as preparation method and application thereof

By epoxidized natural rubber coating and vulcanization treatment on the surface of the positive electrode active material of lithium battery, the microcracks and side reaction problems of high-nickel ternary positive electrode active material during the circulation process are solved, extending the cycle life of the lithium battery and improving its stability.

CN119905531AActive Publication Date: 2025-04-29HUBEI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311401420.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The microcracks and transition metal dissolution, lithium-nickel mixing and phase change of high-nickel ternary positive electrode active materials during the circulation process seriously affect the life of lithium-ion batteries.

Method used

By epoxidizing natural rubber polymer coating on the surface of the positive electrode active material of lithium battery and vulcanizing, a network-like structure is generated to inhibit the generation of microcracks of the positive electrode active material particles during the charge and discharge process.

Benefits of technology

It extends the cycle life of lithium batteries, improves the structural integrity and thermal stability of the positive electrode active material, and reduces harmful side reactions between the electrode and the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905531A_ABST
    Figure CN119905531A_ABST
Patent Text Reader

Abstract

The invention provides an epoxidized natural rubber coated lithium battery positive electrode active material and a preparation method and application thereof, and the preparation method comprises the following steps: 1) dissolving epoxidized natural rubber in toluene, and adding dicumyl peroxide (DCP) for dissolving; 2) taking the solution prepared in the step 1), adding positive electrode active material particles, heating and stirring; and 3) vulcanizing the material obtained in the step 2). According to the invention, the epoxidized natural rubber is used as a coating layer of the positive electrode active material particles, so that the volume expansion of the positive electrode active material and the harmful side reaction between the electrode and the electrolyte can be inhibited in the charging and discharging process of the lithium battery. And under the coating of the epoxidized natural rubber, the coated positive electrode active material can have very good cycle stability compared with the traditional electrode material under the condition of high magnification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to an epoxidized natural rubber-coated lithium battery positive electrode active material, a preparation method and an application thereof. Background Art

[0002] With the development of energy in human society and the multifunctionalization of social reserves, the new energy industry is in an unprecedented period of development. As the core component of the widely used new energy industry, lithium-ion batteries have many advantages such as low production and maintenance costs, environmental friendliness, and long service life. The positive active material of lithium-ion batteries provides the Li required for lithium embedding compounds between the positive and negative electrodes. + , and at the same time help form a solid electrolyte interface (SEI) film. The new ternary cathode active material has excellent discharge specific capacity and charge and discharge rate. However, microcracks, transition metal dissolution, lithium-nickel mixing and phase change of high-nickel ternary cathode active materials during the cycle process will trigger a series of adverse side reactions, which will seriously affect the life of lithium-ion batteries.

[0003] Surface modification through coating is an effective solution to solve the parasitic reaction at the interface between the positive electrode active material and the electrolyte. This surface coating forms an artificial physical barrier on the surface of the electrochemically active positive electrode particles to act as a protective passivation film to prevent direct contact between the positive electrode active material and the electrolyte. It can not only enrich the electrochemical properties of nickel-rich NCM materials, improve the structural integrity and thermal stability of NCM, but also stabilize the interface between the electrode and the electrolyte, preventing the NCM surface phase from changing from layered to rock salt or disordered spinel-like structure. Polymer coating materials are more abundant than inorganic coating materials and have unique properties. They form a surface film with high ionic conductivity on the NCM surface, helping to improve the charge transfer at the positive electrode / electrolyte interface. Due to the flexibility of the polymer itself, compared with inorganic coating materials, it can better adapt to the volume changes of the cathode material during the cycle and more effectively reduce the formation of microcracks on the NCM surface. Summary of the invention

[0004] The present invention uses epoxidized natural rubber to polymer-coat the surface of the positive electrode active material of the lithium battery. Through vulcanization treatment, a network structure is in situ generated on the surface of the positive electrode active material to inhibit the generation of microcracks in the positive electrode active material particles during the charging and discharging process, thereby extending the cycle life of the battery.

[0005] In order to achieve the above object, the present invention provides a method for coating a positive electrode active material with epoxidized natural rubber, comprising the following steps:

[0006] 1) dissolving epoxidized natural rubber in toluene, and adding dicumyl peroxide (DCP) to dissolve;

[0007] 2) taking the solution prepared in step 1), adding positive electrode active material particles, heating and stirring;

[0008] 3) subjecting the material in step 2) to vulcanization treatment.

[0009] According to an embodiment of the present invention, in step 1), the mass ratio of dicumyl peroxide to epoxidized natural rubber is (0.001-0.1):1, for example (0.005-0.08):1, such as 0.01:1.

[0010] According to an embodiment of the present invention, the epoxidation degree of the epoxidized natural rubber in step 1) is 10-60%, such as 20-60%, such as 50%.

[0011] According to an embodiment of the present invention, the epoxidized natural rubber in step 1) is a high-performance rubber obtained by epoxidation modification of natural rubber. Due to the addition of polar epoxy groups, the polarity of natural rubber molecules and the intermolecular interaction force are enhanced.

[0012] According to an embodiment of the present invention, in step 2), the positive electrode active material is a ternary positive electrode active material (NCM), lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, a lithium-rich manganese-based positive electrode active material, preferably NCM622.

[0013] According to an embodiment of the present invention, the mass ratio of the positive electrode active material particles added in step 2) to the epoxidized natural rubber in step 1) is 1:(0.001-0.05), for example, 1:(0.005-0.02), 1:(0.008-0.012), 1:(0.009-0.011), such as 1:0.01, 1:0.005 or 1:0.02.

[0014] According to an embodiment of the present invention, in step 2), the mixture is heated and stirred at 35-50° C. for 1-12 hours.

[0015] According to an embodiment of the present invention, after the stirring is completed in step 2), ultrasonication is performed for more than 10 minutes, for example, ultrasonication for 30 minutes.

[0016] According to an embodiment of the present invention, after the stirring in step 2) is completed, a rotary evaporation treatment is further performed, and the rubber is uniformly coated on the surface of the positive electrode particles by continuous rotary evaporation.

[0017] According to an embodiment of the present invention, after step 2) the coating is completed, a drying treatment is further performed, and the dried material is vulcanized in a flat plate vulcanizer, thereby preparing a positive electrode active material coated with epoxidized natural rubber having a network structure.

[0018] According to an embodiment of the present invention, the vulcanization treatment in step 3) is carried out in a flat plate vulcanizer.

[0019] According to an embodiment of the present invention, the sulfurization treatment in step 3) is heating at 100-180° C. for 1-30 minutes.

[0020] In a preferred embodiment, the epoxidized natural rubber coated positive electrode active material is prepared by the following steps:

[0021] S1) taking a certain amount of epoxidized natural rubber latex, washing it in anhydrous ethanol, then drying it, and after drying, masticating it in a masticator for 30-50 times;

[0022] S2) adding toluene to dissolve the epoxidized natural rubber dried and plasticized in step 1; after the rubber is completely dissolved, adding dicumyl peroxide to continue dissolving;

[0023] S3) placing the positive electrode active material in the epoxidized natural rubber solution containing dicumyl peroxide in step S2), stirring at 35-50° C., and then ultrasonicating;

[0024] S4) performing rotary evaporation in a rotary evaporator; and then continuing to dry the positive electrode active material in a blast oven and a vacuum oven;

[0025] S5) The dried positive electrode active material is heated at 100-180° C. for more than 1 minute for vulcanization treatment to obtain a positive electrode active material coated with epoxidized natural rubber having a network structure.

[0026] The present invention also provides a positive electrode active material coated with epoxidized natural rubber prepared by the method described above.

[0027] The present invention also provides the use of the positive electrode active material coated with epoxidized natural rubber prepared by the above method as a positive electrode material for a lithium battery.

[0028] Beneficial effects of the present invention

[0029] The present invention adopts a rotary evaporator for in-situ coating. Since the solution rotates and flows continuously during the coating process, the coating material is retained on the positive electrode active material to the maximum extent. The preparation process of the present invention is simple, and a good coating effect can be achieved. At the same time, the requirements of this method on the positive electrode material are not strict. Due to the plasticizing treatment, the epoxidized natural rubber can be well dissolved in toluene. In addition, the epoxidized natural rubber itself has very good mechanical properties, and the mechanical properties of the epoxidized natural rubber after vulcanization treatment are greatly improved. Selecting epoxidized natural rubber as a coating layer can inhibit the volume expansion of the positive electrode active material and the harmful side reactions between the electrode and the electrolyte during the charging and discharging process of the lithium battery, and under the coating of the epoxidized natural rubber, the positive electrode active material can have very good cycle stability under high rate conditions relative to traditional electrode materials. Compared with the inorganic material coating method, the epoxidized natural rubber used in the present invention has better flexibility, and at the same time has the advantages of wide source, low cost, simple operation, suitable for large-scale industrial production, etc., and is easy to realize commercialization.

[0030] The epoxidized natural rubber selected by the present invention not only retains the high elasticity, high wear resistance and stress-induced crystallization characteristics of the epoxidized natural rubber after coating, but also greatly improves the anti-slip property, oil resistance, air tightness, adhesion and compatibility with fillers, and has broad application prospects. Through heat vulcanization treatment, the epoxidized natural rubber is transformed from a linear structure to a highly elastic network structure, casting a soft protective layer for the positive electrode active material. Compared with the sulfur vulcanization method commonly used, the selected diisopropylbenzene peroxide vulcanization method has good latex stability, less non-rubber components and large elongation. The bond energy of the CC bond produced by its vulcanization is greater than the single sulfur, disulfide and polysulfide bonds produced by the sulfur vulcanization system. At the same time, the structure of the epoxidized natural rubber has a very rich structural designability, which makes the coating layer have unlimited possibilities for performance improvement.

[0031] In summary, for positive electrode active materials, the improvements of the coating layer include: (1) The coating layer will produce a reaction force on the volume expansion of the active particles, dispersing the mechanical stress inside the positive electrode material particles, thereby reducing the generation of microcracks on the surface of the active particles. (2) The flexible network formed by the coating layer not only inhibits the breakage of the positive electrode active material, but also reduces the contact area between the electrolyte and the positive electrode active material, thereby inhibiting the harmful side reactions between the positive electrode active material and the electrolyte. (3) The coating layer has a certain ability to conduct electrons and ions. While acting as a surface chemical modifier for ion charge transfer at the cathode / electrolyte interface, it will not affect the discharge specific capacity of the positive electrode active material itself. (4) The coating material is derived from natural materials, which is cheap and easy to obtain. This coating process adheres to the green and environmental protection concept of battery energy. Therefore, the use of structurally designed epoxidized natural rubber as a coating layer has a lot of room for optimization of the performance of the positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a high-magnification scanning electron microscope photo of unmodified pure NCM622.

[0033] Figure 2 This is a high-magnification scanning electron microscope photograph of NCM622 coated with 0.5 wt% epoxidized natural rubber in Example 2.

[0034] Figure 3 This is a high-magnification scanning electron microscope photograph of NCM622 coated with 1 wt% epoxidized natural rubber in Example 1.

[0035] Figure 4 This is a high-magnification scanning electron microscope photograph of NCM622 coated with 2 wt% epoxidized natural rubber in Example 3.

[0036] Figure 5 The unmodified pure NCM622 in Example 1 is assembled into a full battery, activated at a cut-off voltage of 2.5-4.3V and a current density of 0.2C, and the specific capacity-voltage curve at a current density of 0.5C.

[0037] Figure 6 In Example 2, 0.5 wt% epoxidized natural rubber-coated NCM622 was assembled into a full battery, activated at a cut-off voltage of 2.5-4.3 V and a current density of 0.2C, and the specific capacity-voltage curve at a current density of 0.5C.

[0038] Figure 7 The full battery is assembled with 1 wt% epoxidized natural rubber coated NCM622 in Example 1, activated at a cut-off voltage of 2.5-4.3 V and a current density of 0.2C, and the specific capacity-voltage curve at a current density of 0.5C.

[0039] Figure 8 The full battery is assembled with 2 wt% epoxidized natural rubber coated NCM622 in Example 3, activated at a cut-off voltage of 2.5-4.3 V and a current density of 0.2C, and the specific capacity-voltage curve at a current density of 0.5C.

[0040] Fig. 9 This is a schematic diagram of the long cycle performance test results of the full battery assembled with the unmodified pure NCM622 in Example 1 at a cut-off voltage of 2.5-4.3V and a current density of 0.5C.

[0041] Fig.10It is a schematic diagram of the long cycle performance test results of a full battery assembled with 0.5wt% epoxidized natural rubber-coated NCM622 in Example 2 at a cut-off voltage of 2.5-4.3V and a current density of 0.5C.

[0042] Fig.11 It is a schematic diagram of the long cycle performance test results of a full battery assembled with 1wt% epoxidized natural rubber-coated NCM622 in Example 1 at a cut-off voltage of 2.5-4.3V and a current density of 0.5C.

[0043] Fig.12 It is a schematic diagram of the long cycle performance test results of a full battery assembled with 2wt% epoxidized natural rubber-coated NCM622 in Example 3 at a cut-off voltage of 2.5-4.3V and a current density of 0.5C.

[0044] Fig.13 This is a schematic diagram comparing the long cycle performance test results of a full battery assembled with the unmodified pure NCM622 in Example 1 and NCM622 with different coating concentrations at a cut-off voltage of 2.5-4.3V and a current density of 0.5C.

[0045] Fig.14 This is the specific capacity-voltage curve of the unmodified pure NCM622 assembled into a full battery in Example 1, activated at a cut-off voltage of 2.5-4.3V and a current density of 0.2C, and at a current density of 1C.

[0046] Fig.15 The full battery is assembled with 1 wt% epoxidized natural rubber coated NCM622 in Example 1, activated at a cut-off voltage of 2.5-4.3 V and a current density of 0.2 C, and the specific capacity-voltage curve at a current density of 1 C.

[0047] Fig.16 It is a schematic diagram comparing the long cycle performance test results of a full battery assembled from the unmodified pure NCM622 in Example 1 and the NCM622 coated with 1wt% epoxidized natural rubber in Example 1 at a cut-off voltage of 2.5-4.3V and a current density of 1C.

[0048] Fig.17 This is a high-magnification scanning electron microscope photograph of the ion beam cross-section of the unmodified pure NCM622 in Example 1 after 500 cycles at a 1C rate.

[0049] Fig.18 This is a high-magnification scanning electron microscope photograph of the ion beam cross section of NCM622 coated with 1 wt% epoxy natural rubber in Example 1 after 500 cycles at 1C rate.

[0050] Fig.19This is a transmission electron microscope photograph of the coating layer of NCM622 coated with 1 wt % epoxy natural rubber in Example 1.

[0051] Fig. 20 This is the EDS element distribution diagram of NCM622 coated with 1 wt% epoxy natural rubber in Example 1.

[0052] Fig.21 It is a comparison of stress-strain curves of epoxy natural rubber before and after vulcanization.

[0053] Fig. 22 This is a schematic diagram of the long cycle performance test results of a full battery assembled from unvulcanized 1wt% epoxy natural rubber-coated NCM622 in Example 1, activated at a cut-off voltage of 2.5-4.3V and a current density of 0.2C, and at a current density of 0.5C. DETAILED DESCRIPTION

[0054] The method of the present invention is described below by means of specific examples, but the present invention is not limited thereto, and any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0055] The present invention provides an in-situ coating method based on a lithium battery positive electrode active material, which specifically comprises the following steps:

[0056] 1) Take a certain amount of epoxidized natural rubber latex, wash it several times in anhydrous ethanol, and then dry it. After drying, masticate it in a masticator for 30-50 times.

[0057] 2) Weigh 50 mg of dried and plasticized epoxidized natural rubber, add 20 ml of toluene and dissolve. After it is completely dissolved, add 0.5 mg of diisopropylbenzene peroxide and continue dissolving.

[0058] 3) Weigh 500 mg of NCM622 positive electrode active material and place it in the epoxidized natural rubber solution containing dicumyl peroxide, stir at 40 degrees for 3 hours, and then ultrasonicate for half an hour.

[0059] 4) performing a rotary evaporation treatment in a rotary evaporator; and then continuing to dry the positive electrode active material in a forced air oven and a vacuum oven.

[0060] 5) The dried positive electrode active material is heated at 160 degrees for 12 minutes for vulcanization treatment. Finally, the epoxidized natural rubber-coated NCM622 positive electrode active material with a network structure is obtained.

[0061] The in-situ coating method of epoxidized natural rubber provided by the present invention is simple to operate, can well form a coating layer on the positive electrode active material, and through further vulcanization treatment, the prepared epoxidized natural rubber has good mechanical strength. The coating layer formed on the surface of the positive electrode active material can inhibit the volume expansion problem of the positive electrode active material during the charging and discharging process, reduce harmful side reactions at the positive electrode / electrolyte interface, and greatly extend the cycle life of the lithium battery during the charging and discharging process.

[0062] The coating layer in the present invention can maintain good stability of the positive electrode active material during long-term high-rate cycling. In addition, due to the structural designability of epoxidized natural rubber, the performance of the coating layer has a lot of room for improvement. And the method is simple in process and can be well used in industrial production.

[0063] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0064] Preparation Example 1

[0065] Take a certain amount of epoxidized natural rubber latex (epoxidation degree of 50%, average molecular weight of about 350,000), wash it several times in anhydrous ethanol, and dry it. Then, plasticize it 30 times in a plasticizer to prepare epoxidized natural rubber. The stress-strain curve comparison of epoxidized natural rubber before and after vulcanization is shown in the figure below. Fig.21 As shown. Fig.21 It can be seen that the mechanical properties of the vulcanized epoxidized natural rubber are significantly improved compared with the unvulcanized epoxidized natural rubber.

[0066] Example 1

[0067] (I) Preparation of 1wt% epoxidized natural rubber coated NCM622 positive electrode active material

[0068] Weigh 500 mg of NCM622 positive electrode active material and place it in a coating solution containing 5 mg of epoxidized natural rubber (the preparation process of the coating solution is: weigh 50 mg of dried and plasticized epoxidized natural rubber, add 20 ml of toluene, and dissolve it. After it is completely dissolved, add 0.05 mg of diisopropylbenzene peroxide and continue the dissolution process). Stir at 40 degrees for 3 hours, and then ultrasonicate for half an hour.

[0069] The positive electrode active material was dried in a rotary evaporator and then in a vacuum oven.

[0070] The dried positive electrode active material was heated at 160 degrees for 12 minutes for vulcanization treatment. Finally, a network-structured epoxidized natural rubber-coated NCM622 positive electrode active material was obtained. Figure 3It can be seen from the scanning electron micrograph that 1wt% epoxidized natural rubber is successfully coated on the surface of NCM622 particles.

[0071] (II) Assembling the full battery and studying its performance

[0072] The lithium sheet was used as the negative electrode of the full battery. The 1wt% epoxidized natural rubber coated NCM622 positive electrode active material prepared in step (I) was taken, conductive carbon black (Ketjen black) was added, PVDF was used as a binder, and a slurry coating was prepared with a mass ratio of positive electrode active material: conductive carbon black: PVDF of 8:1:1. The electrode sheet obtained by vacuum drying was used as the positive electrode. The full battery was assembled using PP diaphragm, nickel foam and LiPF6 electrolyte containing 2% VC+EC / DEC / DMC mixed solvent. The surface capacity of 1wt% epoxidized natural rubber coated NCM622 positive electrode material is 3mAh cm -2 The cut-off voltage of the test was about 2.5-4.3V, the test temperature was 25°C, the current density was 0.2C for five activation cycles, and the current density was 0.5C for cycling. Fig.11 The reversible capacity of the full battery was shown to be maintained at 150 mAh g after 300 cycles. -1 . Figure 7 The charge and discharge curves are shown, and it can be seen that the charge and discharge reversibility is good and the polarization is small. Fig.19 Transmission electron microscopy photograph of the coating layer of NCM622 coated with 1wt% epoxidized natural rubber. Fig. 20 This is the EDS element distribution diagram of 1wt% epoxidized natural rubber coated NCM622 particles. It can be seen that C and O elements are evenly distributed on the NCM622 particles, indicating that the present application successfully prepared epoxidized natural rubber coated NCM622 particles.

[0073] Comparative Example 1

[0074] The other conditions were the same as those in Example 1, except that an uncoated NCM622 positive electrode active material was used.

[0075] from Fig. 9 It can be seen that the reversible capacity of the assembled full battery is maintained at 100 mAh g after 300 cycles. -1 Since it does not have an epoxidized natural rubber coating, during the cycle of the full battery, the positive electrode active material will produce more serious microcracks, transition metal dissolution, lithium-nickel mixing, and phase transition from layered to rock salt or disordered spinel structure, and a series of side reactions that are not conducive to the life of lithium-ion batteries, ultimately leading to battery failure. Fig.17 Uncoated pure NCM622 and Fig.18The high-magnification scanning electron microscope photograph of the ion beam cross-section of the 1wt% coated NCM622 positive electrode particles after 500 cycles at 1C rate can intuitively show the protective effect of the coating layer on pure NCM622.

[0076] Example 2

[0077] The other conditions were the same as those in Example 1, except that a coating solution containing 2.5 g of epoxidized natural rubber was selected in step 1). Figure 2 In the scanning electron micrograph, it can be observed that 0.5wt% epoxidized natural rubber coated NCM622 particles. Figure 2 It can be seen that 0.5 wt% epoxidized natural rubber is successfully coated on the surface of NCM622 particles.

[0078] from Fig.10 It can be seen that the reversible capacity of the assembled full battery is maintained at 113 mAh g after 300 cycles. -1 . Figure 6 Display its charge and discharge curve.

[0079] Example 3

[0080] The difference from Example 1 is that in step 1), a coating solution containing 10 g of epoxidized natural rubber is selected. Figure 4 In the scanning electron micrograph of the 2wt% epoxidized natural rubber coated NCM622 particles, it can be observed that Figure 4 It can be seen that 2 wt% epoxidized natural rubber is successfully coated on the surface of NCM622 particles.

[0081] from Fig.12 It can be seen that the reversible capacity of the full battery is maintained at 117 mAh g after 300 cycles. -1 , Figure 8 Display its charge and discharge curve.

[0082] Comparative Example 2

[0083] Referring to the method in Example 1, the difference from Example 1 is that no vulcanization treatment is performed to prepare unvulcanized 1wt% epoxy natural rubber coated NCM622. It is assembled into a battery according to the method in Example 1, activated at a cut-off voltage of 2.5-4.3V and a current density of 0.2C. The long cycle performance test results at a current density of 0.5C are as follows: Fig. 22 The results show that the battery assembled by the uncured epoxy natural rubber coated NCM622 has a reversible capacity of 300 cycles and a specific capacity of 116 mAh g -1Therefore, the coating layer of Example 1 of the present application is subjected to sulfurization treatment, so that the coating layer can more effectively suppress the volume expansion of the positive electrode active material and the harmful side reactions between the electrode and the electrolyte during the charging and discharging process of the lithium battery. Under the condition of 0.5C rate, the positive electrode material coated with the unsulfurized coating layer has significantly better cycle stability.

[0084] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for coating a positive electrode active material with epoxidized natural rubber, characterized in that: The steps include: 1) dissolving epoxidized natural rubber in toluene, and adding dicumyl peroxide (DCP) to dissolve; 2) taking the solution prepared in step 1), adding positive electrode active material particles, heating and stirring; 3) subjecting the material obtained in step 2) to a vulcanization treatment.

2. The method according to claim 1, characterized in that In step 1), the mass ratio of dicumyl peroxide to epoxidized natural rubber is (0.001-0.1):

1.

3. The method according to claim 1 or 2, characterized in that: Step 1) The epoxidation degree of the epoxidized natural rubber is 10-60%.

4. The method according to any one of claims 1 to 3, characterized in that: In step 2), the positive electrode active material is a ternary positive electrode active material (NCM), lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, or a lithium-rich manganese-based positive electrode active material. Preferably, the mass ratio of the positive electrode active material particles added in step 2) to the epoxidized natural rubber in step 1) is 1:(0.001-0.05).

5. The method according to any one of claims 1 to 4, characterized in that: In step 2), the mixture is heated and stirred at 35-50° C. for 1-12 hours.

6. The method according to any one of claims 1 to 5, characterized in that: After the stirring in step 2) is completed, ultrasonication is performed for more than 10 minutes. Preferably, after the stirring in step 2) is completed, a rotary evaporation treatment is further performed, and the epoxidized natural rubber is uniformly coated on the surface of the positive electrode particles by continuous rotary evaporation.

7. The method according to any one of claims 1 to 6, characterized in that: In step 3), the vulcanization treatment is carried out in a flat plate vulcanizer. Preferably, the sulfurization treatment in step 3) is performed by heating at 100-180° C. for 1-30 minutes.

8. The method according to any one of claims 1 to 7, characterized in that: The epoxidized natural rubber coated positive electrode active material was prepared by the following steps: S1) taking a certain amount of epoxidized natural rubber latex, washing it in anhydrous ethanol, then drying it, and after drying, masticating it in a masticator for 30-50 times; S2) adding toluene to dissolve the epoxidized natural rubber dried and plasticized in step 1, and adding dicumyl peroxide to continue dissolving after the rubber is completely dissolved; S3) placing the positive electrode active material in the epoxidized natural rubber solution containing dicumyl peroxide in step S2), stirring at 35-50° C., and then ultrasonicating; S4) performing rotary evaporation in a rotary evaporator; and then continuing to dry the positive electrode active material in a blast oven and a vacuum oven; S5) The dried positive electrode active material is heated at 100-180° C. for more than 1 minute for vulcanization treatment to obtain a positive electrode active material coated with epoxidized natural rubber having a network structure.

9. The positive electrode active material coated with epoxidized natural rubber prepared by the method according to any one of claims 1 to 8.

10. Use of the positive electrode active material coated with epoxidized natural rubber prepared by the method according to any one of claims 1 to 8 as a positive electrode material for lithium batteries.

Citation Information

Patent Citations

  • Preparation methods of nano-coated positive electrode materials and secondary aluminium cell using nano-coated positive electrode materials

    CN101662021A

  • Epoxidized natural rubber coated modified white carbon black and preparation method thereof and rubber material

    CN105330899A

  • Composite positive electrode material and preparation method and application thereof

    CN115863595A

  • Surface-modified positive electrode material as well as preparation method and application thereof

    CN115881954A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    US20080118841A1